STRATEGI GURU DALAM MENGAJARKAN MEMBACA PERMULAAN ANAK USIA 4-5 TAHUN - Lestari, Dyah Ayu (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
The teaching process requires strategies so that learning activities become easier, more comfortable and get the intended results. The purpose of this study is to find out more about the stages of the strategies used by teachers in teaching children aged 4-5 years in the Jami' Grand Mosque Kindergarten in Malang and also the results of the strategies used. This research uses a qualitative approach and type of case study research because this research will further analyze how the strategies used by teachers in teaching beginning reading to children aged 4-5 years, namely group A in three classes. the instrument of this research is the researcher himself, with data collection techniques using interviews, observation notes, and documentation. The data analysis process refers to Miles and Huberman, namely by reducing data, presenting data and drawing conclusions. The results showed that the strategies used by teachers in teaching beginning reading to 4-5 year old children included direct learning strategies, individualized learning strategies, and group learning strategies. While the results of the strategies that have been applied make most of the group A children aged 4-5 years have the ability to read beginning. This can be seen from the characteristics that appear according to the standards of child development achievement.